Immunohistochemical co-expression of PAX2 and CAIX predicts better prognosis in clear cell renal cell carcinoma after nephrectomy: A retrospective observational study: PAX2 and CAIX co-expression predicts clear cell RCC prognosis - Shao, Honggang; Liao, Yougang; Xiang, Min; Hu, Deng; Liu, Sha (Cellular and Molecular Biology, 2024)
Clear cell renal cell carcinoma (ccRCC) is a lethal malignancy with high metastatic probability. Paired box 2 gene product (PAX2) carbonic anhydrase IX were biomolecules closely linked with ccRCC development and outcomes of multiple malignancies. We aim to explore the role of immunohistochemical staining of PAX2 and CAIX to predict ccRCC prognosis after nephrectomy. Surgical specimens of patients who were pathologically diagnosed as ccRCC were reviewed. Expression levels of PAX2 and CAIX were assessed via immunohistochemical staining. Recurrence-free survival (RFS) and overall survival were compared among different phenotypes. Inverse probability of treatment weighting (IPTW) was used for adjustment of confounding factors. 56 patients were included. Patients with PAX2 and CAIX high-expression (the two-high group, n=8) had significantly longer RFS and OS than those of simultaneously down-expression (the two-low group, n=31). Median RFS was 38.4 (95% CI: 32.3-NA) for the two-high group and 14.8 (95% CI: 13.4-39.0) months for the two-low group (P=0.043). IPTW confirmed PAX2 and CAIX co-expression is associated with less recurrence risk HR: 0.39, 95% CI: 0.17-0.92, P=0.031). Co-expression of PAX2 and CAIX is associated better prognosis of ccRCC. We are looking for validation by large cohort studies.